Biological Response to the Interaction of a Mesoscale Eddy and the River Plume in the Northern South China Sea. Issue 9 (26th August 2021) - Geng, Bingxu; Xiu, Peng; Liu, Na; He, Xianqiang; Chai, Fei
Abstract: The Pearl River delivers a large amount of freshwater, sediments and nutrients to the northern shelf of the South China Sea (SCS). In June 2015, an anomalously strong phytoplankton bloom was captured by satellite images in the slope region of the northern SCS, which was associated with the southeastward spreading of the river plume on the shelf and a southwestward‐moving eddy along the slope. In this study, the underlying dynamics triggering the bloom was investigated using a coupled physical‐biogeochemical model. Results show that the nutrients supporting the bloom were not directly sourced from the Pearl River, but were transported locally from subsurface. The eddy cross‐slope current advected low salinity water from the Pearl River plume, which interacted with eddy edge and enhanced frontal dynamics with vertical motions. The front‐induced upwelling injected nutrients from subsurface to surface layer and stimulated phytoplankton bloom in the upper layer. Overall, the phytoplankton bloom was attributable to the interaction of freshwater plume on top and the eddy edge induced anomaly in the subsurface. These findings suggest that the eddy‐entrained freshwater could have significant biological consequences through modifying local dynamics in the plume‐influenced region. Plain Language Summary: The Pearl River plume mostly spreads on the shelf of the northern South China Sea (SCS). In June 2015, the plume was advected to the slope region by an eddy. Meanwhile, satellite captured a strong phytoplankton bloom on the slope with high chlorophyll concentration that appeared to be connected with the high chlorophyll concentration in the plume water on the shelf. With a numerical model, this study found that nitrate concentration was high at the river estuary, but it decreased quickly along the river plume on the shelf. When the plume water reached the slope region, nitrate concentration was comparable to that in surrounding waters. The advected freshwater in the plume interacted with the eddy and enhanced local front at the eddy edge, which drives vertical nutrient injection and stimulates the anomalous phytoplankton bloom in the upper layer. Key Points: An anomalous phytoplankton bloom occurred in the slope region under the influence of a mesoscale eddy and the Pearl River Plume The nutrients supporting the bloom were not directly sourced from the Pearl River but were injected locally from subsurface The interaction of freshwater from the Pearl River and eddy edge enhances frontal dynamics facilitating nutrient transport